Perioperative hypothermia and associated factors: A prospective cohort study - ABDULLAYEV, RUSLAN; UMUROĞLU, TÜMAY (My University, 2023)
Objective: Perioperative hypothermia is deleterious with many consequences, including coagulopathy, decreased immune functions, prolonged drug clearance, and cardiovascular complications. In this study we aimed to demonstrate the incidence of perioperative hypothermia during general anesthesia, its associated risk factors, and outcomes. Methods: For this prospective cohort study patients aged 18-75 years with American Society of Anesthesiologists physical status I-III scheduled for any elective operation under general anesthesia in a one-month period were recruited. The patients’ body temperatures were measured in the preoperative unit, in the operating theatre before induction, at the second hour of the operation, at the end of the operation, at the postoperative recovery unit admission, and discharge using a medical infrared thermometer. The patients’ demographic and hemodynamic characteristics, magnitudes of surgery, surgery and anesthesia durations, warming methods, hospital and Intensive Care Unit (ICU) length of stays were recorded. Results: Sixty five out of 290 enrolled patients (22.4%) developed perioperative hypothermia. Anesthesia and surgery time was longer in patients with hypothermia (p<0.001). Hospital length of stay of the patients was also longer in the patients with hypothermia (p<0.001). Intensive care unit admission of the patients with hypothermia was significantly higher compared with those with normothermia (2.7 vs 9.2%, p=0.030). Conclusion: Perioperative hypothermia continues to be a challenge despite many published clinical application guidelines in this context. Intermediate and major type surgeries resulted in more perioperative hypothermia. Perioperative hypothermia was significantly associated with longer operation and anesthesia durations, hospital length of stays, and higher ICU admissions as well. Routine monitoring and active warming should be performed throughout the perioperative period to prevent hypothermia and current practice guidelines should be followed.

Amaç: Perioperatif hipotermi, koagülopati, azalmış bağışıklık fonksiyonları, uzamış ilaç klirensi ve kardiyovasküler komplikasyonlar dahil olmak üzere birçok sonucu olan zararlı bir durumdur. Bu çalışmada genel anestezi sırasında perioperatif hipotermi insidansını, ilişkili risk faktörlerini ve sonuçlarını göstermeyi amaçladık. Yöntem: Bu prospektif kohort çalışma için, bir aylık bir süre içinde genel anestezi altında herhangi bir elektif operasyon planlanan Amerikan Anesteziyologlar Derneği fiziksel durumu I-III olan 18-75 yaş arası hastalar alındı. Hastaların vücut sıcaklıkları preoperatif ünitede, ameliyat salonunda indüksiyondan önce, operasyonun ikinci saatinde, operasyon sonunda; ameliyat sonrası derlenme ünitesinin girişinde ve çıkışında tıbbi kızılötesi termometre kullanılarak ölçüldü. Hastaların demografik ve hemodinamik özellikleri, cerrahi büyüklükleri, ameliyat ve anestezi süreleri, ısıtma yöntemleri, hastane ve yoğun bakım ünitesin (YBÜ) yatış süreleri kaydedildi. Bulgular: Kayıtlı 290 hastanın altmış beşinde (%22,4) perioperatif hipotermi gelişti. Anestezi ve cerrahi süresi hipotermili hastalarda daha uzundu (p<0,001). Hastaların hastanede kalış süreleri de hipotermisi olan hastalarda daha uzundu (p<0,001). Hipotermili hastaların yoğun bakıma yatışları normotermili hastalara göre anlamlı olarak daha yüksekti (%2,7’ye karşı %9,2, p=0,030). Sonuç: Perioperatif hipotermi, bu bağlamda yayınlanan birçok klinik uygulama kılavuzuna rağmen sorun olmaya devam etmektedir. Orta büyüklükte ve majör tip ameliyatlar daha fazla perioperatif hipotermi ile sonuçlandı. Perioperatif hipotermi, daha uzun operasyon ve anestezi süreleri, hastanede kalış süreleri ve daha yüksek YBÜ yatışları ile de anlamlı şekilde ilişkiliydi. Hipotermiyi önlemek için perioperatif dönem boyunca rutin monitörizasyon ve aktif ısıtma yapılmalı, bu konuda güncel uygulama kılavuzları takip edilmelidir.
Perioperatif hipotermi ve ilişkili faktörler: Prospektif kohort çalışma
Keywords: Tıp; Cerrahi Tıp Bilimleri; Anesteziyoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ANESTEZİYOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ANESTHESIOLOGY; Anesteziyoloji ve Ağrı Tıbbı; Anesthesiology and Pain Medicine; Hypothermia; incidence; length of stay; rewarming; risk factor; Hipotermi; insidans; yatış süresi; risk faktörü; ısıtma